Gulbenkiania mobilis gen. nov., sp. nov., isolated from treated municipal wastewater - Vaz-Moreira, Ivone (2011)
A bacterial strain (E4FC31T) isolated from treated municipal wastewater was characterized phenotypically and phylogenetically. Cells were Gram-negative, curved rods with a polar flagellum. The isolate was catalase-, oxidase- and arginine dihydrolase-positive, and able to grow between 15 and 45 6C and between pH 5.5 and 9.0. The predominant fatty acids were C16 : 1/iso-C15 : 0 2-OH and C16 : 0, the major respiratory quinone was ubiquinone 8 and the G+C content of the genomic DNA was 63 mol%. 16S rRNA gene sequence analysis indicated that strain E4FC31T belonged to the class Betaproteobacteria and was a member of the family Neisseriaceae. Its closest phylogenetic neighbours were Aquitalea magnusonii and Chromobacterium violaceum (<94% 16S rRNA gene sequence similarity). Phylogenetic analysis and phenotypic characteristics of strain E4FC31T suggest that it represents a novel species of a new genus, for which the name Gulbenkiania mobilis gen. nov., sp. nov. is proposed. The type strain of Gulbenkiania mobilis is E4FC31T (=DSM 18507T=LMG 23770T).